Correlation of matrix metalloproteinase-9 level, erythrocyte sedimentation rate, rheumatoid factor, and the duration of illness with radiological findings in rheumatoid arthritis patients - G Aji; Ida Ayu Ratih Wulansari Manuaba; Jeffrey A Ongkowijaya; Bambang Setiyohadi; Sumariyono Sumariyono (Indonesian Journal of Rheumatology, 2010)
Background: Rheumatoid arthritis (RA) is a common autoimmune disease of the joint indicated by chronic inflammation of synovium, cartilage destruction, and osteopenia. The end results of RA are joint deformity and disability that will decrease the quality of life ofthe patients. Until now there is not a specifi c marker to assess the process of joint and bone damage in RA. Available markers such as C-reactive protein and erythrocyte sedimentation rate (ESR) indicate more about the infl ammatory status of the patient. Thediscovery of matrix metalloproteinases (MMPs) enzyme overexpression in RA has brought a new hope for the discovery of more specifi c markers of joint damage.Objective: To study the correlation of MMP-9 level, ESR, rheumatoid factor (RF), and the duration of illness with joint damage in RA patients.Methods: A cross-sectional study was conducted on RA outpatients in rheumatology clinic at Cipto Mangunkusumo General Hospital, Jakarta from January to October 2009. From the patients who fulfilled the inclusion criteria and did not fulfi ll the exclusion criteria, blood sample was collected for MMP-9 level, RF, and ESR examinations; hand radiography (posterior-anterior view) was also taken. Results: From the study of 46 patients, we found a significant correlation between MMP-9 level and radiographic feature of bone erosion (r = 0.3, p = 0.02) and between the duration of illness and Sharp score (r = 0.36, p = 0.014). There was no correlation between ESR and radiological fi ndings nor between RF and radiological fi ndings. Linear regression analysis showed the duration of illness as the most infl uencing factor toradiological fi ndings in RA patients.Conclusion: We found a signifi cant correlation between MMP-9 level and radiographic feature of bone erosion, and between the duration of illness and radiological fi ndings in RA patients.